Peran Pengetahuan, Sikap, Sarana-Prasarana, Dan Kebijakan Terhadap Perilaku Pengelolaan Sampah Rumah Tangga di Kecamatan Karang Intan Kabupaten Banjar - Ani Kipatul Hidayah; Lenie Marlinae; Laily Khairiyati; Agung Waskito; Husaini Husaini; Anugrah Nur Rahmat; Cieca Tri Sulistia; Maulidah Maulidah; Nurhaliza Putri; Araya Maharani (Jurnal Kesehatan Indonesia, 2025)
Household waste management is a crucial issue that impacts health, the environment, and sustainability. This study aimed to analyze the relationship between knowledge, attitudes, facilities, and policies with household waste management behavior in Karang Intan Subdistrict, Banjar Regency. A cross-sectional design was applied involving 130 respondents selected through random sampling. Data were collected using a structured questionnaire and analyzed using Spearman Rank correlation test. The results showed a positive and significant relationship between knowledge (p = 0.009) and attitudes (p = 0.028) with household waste management behavior. Facilities showed a positive but non-significant relationship (p = 0.082), while policies indicated a significant negative relationship (p = 0.026). In conclusion, increasing knowledge and fostering positive attitudes are key factors in improving household waste management behavior, while the effectiveness of policies requires reinforcement through proper socialization and targeted implementation. Practical implications highlight the need for continuous community education and stronger enforcement of local policies to achieve sustainable household waste management.